2015
DOI: 10.1108/jpmh-06-2013-0040
|View full text |Cite
|
Sign up to set email alerts
|

Mental distress and human rights of asylum seekers

Abstract: Purpose – This paper studies the experiences of asylum seekers in Australia. The purpose of this paper is to explore the relationship between mental wellbeing, living conditions, and Australia’s detention policies in light of human rights. Design/methodology/approach – Using grounded theory, data were collected via observations, semi-structured interviews, key-informant interviews, and document analysis. Participants included seven asylu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…Detention of asylum seekers in Australia certainly does not fulfill these human rights according to the findings presented in this and other research (Bull, Schindeler, Berkman, & Ransley, 2013;Campbell & Steel, 2015;Carrigan, 2014;Triggs, 2014;Woolcott et al, 2013). Given these findings, the authors recommend countries that currently detain people undergoing refugee status determination shift to policies of community placement.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Detention of asylum seekers in Australia certainly does not fulfill these human rights according to the findings presented in this and other research (Bull, Schindeler, Berkman, & Ransley, 2013;Campbell & Steel, 2015;Carrigan, 2014;Triggs, 2014;Woolcott et al, 2013). Given these findings, the authors recommend countries that currently detain people undergoing refugee status determination shift to policies of community placement.…”
Section: Discussionsupporting
confidence: 51%
“…Its government states that it is "committed to not providing permanent protection visas" (Department of Immigration and Border Protection, 2015) to people who arrive by boat without a pre-arranged visa and has, therefore, subjected asylum seekers to detention, offshore arrangements, and harsh conditions in community detention since the introduction of mandatory detention (Campbell & Steel, 2015;Department of Immigration and Border Protection, 2015;Fleay, Hartley, & Kenny, 2013;Fleay & Hoffman, 2014;Phillips & Spinks, 2013). To date, no research has been published describing occupational deprivation and asylum seekers in Australia.…”
Section: Australian Contextmentioning
confidence: 98%
See 1 more Smart Citation
“…Mandatory detention of “unauthorised” arrivals claiming asylum in Australia is arguably the most controversial of these refugee policies. Since 2009, six articles have been published describing the detrimental effect that detention has on the mental health of detainees 10–15 . Green and Eager's examination of asylum seeker health records found that those in detention for longer than 24 months, were 3.6 times as likely to develop new psychiatric illness than those detained for less than 3 months (95% CI, 1.1–11.0) 15 .…”
Section: Methodsmentioning
confidence: 99%
“…Since 2009, six articles have been published describing the detrimental effect that detention has on the mental health of detainees. [10][11][12][13][14][15] Green and Eager's examination of asylum seeker health records found that those in detention for longer than 24 months, were 3.6 times as likely to develop new psychiatric illness than those detained for less than 3 months (95% CI, 1.1-11.0). 15 Coffey et al's qualitative analysis of the experiences of 17 adult refugees who had been detained for, on average, three years demonstrated that three years post-detention participants had poor psychological wellbeing and suffered with a sense of insecurity, injustice, struggles with relationships and overall deficient mental health.…”
Section: Mandatory Detentionmentioning
confidence: 99%